Breast cancer risk in airline cabin attendants: a nested case-control study in Iceland. Issue 11 (22nd October 2003) - Rafnsson, V; Sulem, P; Tulinius, H; Hrafnkelsson, J
Abstract : Aims: To investigate whether length of employment as a cabin attendant was related to breast cancer risk, when adjusted for reproductive factors. Methods: Age matched case-control study nested in a cohort of cabin attendants. The cases were found from a nationwide cancer registry (followed up to end of year 2000) and the reproductive factors (age at first childbirth and number of children) from a registry of childbirth, in both instances by record linkage with the cabin attendants' identification numbers. The employment time of the cabin attendants at the airline companies and the reproductive factors had been systematically recorded prior to the diagnosis of breast cancer in the cohort. A total of 35 breast cancer cases and 140 age matched controls selected from a cohort of 1532 female cabin attendants were included in the study. Results: The matched odds ratio from conditional logistic regression of breast cancer risk among cases and controls of cabin attendants was 5.24 (95% CI 1.58 to 17.38) for those who had five or more years of employment before 1971 compared with those with less than five years of employment before 1971, adjusted for age at first childbirth and length of employment from 1971 or later. Conclusions: The association between length of employment and risk of breast cancer, adjusted for reproductive factors, indicates that occupational factors may be an important cause of breast cancer among cabin attendants; the association is compatible with a long induction period.